NPP supply and demand projections for the Sahel - Sallaba, Florian; Olin, Stefan; Seaquist, Jonathan; Lehsten, Veiko; Engström, Kerstin (Lund University, 2017)
Annual projections of different NPP (net primary production) scenarios balance (supply and demand) for the 21st century Sahel. Projections are generated by coupling a simple NPP supply model (forced with projections from four representative concentration pathways) with a global, reduced-complexity demand model (driven by socio-economic data and assumptions derived from five shared socio-economic pathways). Corresponding population density projections are also included in the dataset.
This data is supplementary to Sallaba, F., Olin, S., Engström, K., Abdi, A. M., Boke-Olén, N., Lehsten, V., Ardö, J., and Seaquist, J. W.:(2017) Future supply and demand of net primary production in the Sahel, Earth System. Dynamics.
Keywords: Environmental Sciences; Miljövetenskap